ETD: Symptoms and Intraoperative findings in patients undergoing revision fundoplication - Etalleb, Mohamed (Division of General Surgery, 2025)
Approximately 20% of patients who undergo anti-reflux surgery will report a recurrence of reflux symptoms or develop new symptoms, with 5% ultimately requiring revision fundoplication. The aim of this study is to document symptoms at representation, pre-operative work-up and intraoperative findings of patients presenting for revision fundoplication (RF). Methods: This is a single center descriptive retrospective review of 37 patients who required revision of a previous fundoplication for significant recurrent symptoms between January 2015 and December 2017 at Groote Schuur Hospital and UCT Private Academic Hospital. Patient data included demographics, body mass index (BMI), patient reported symptoms prompting initial fundoplication, interval to symptom recurrence and RF, technique of the first and subsequent revision surgery and perioperative morbidity. Recurrent symptoms at representation, results of pre-operative investigations and actual intraoperative assessment during RF were reviewed. Results: During the two-year study period 37 patients underwent RF. The mean age was 52.9 years (range 22 – 77 years, SD =13.3), with 25 (67.6%) females and 12 (32.4%) males included in the cohort. The most frequent patient-reported indication for index fundoplication was gastro- oesophageal reflux (GOR) (65%). Symptoms at representation prior to RF included dysphagia (51.4%) and heartburn (51.4%) equally, epigastric pain (48.6%), volume reflux (43.2%), atypical chest pain (24.3%), bloating (16.2%), nausea (13.5%) and early satiety (10.8%). The most observed endoscopic finding (available in 35 patients) was a recurrent sliding hiatus hernia (42.9%). All had a contrast swallow with evidence of delayed transit into the stomach present in 45.9%, recurrent sliding hernia and dilated distal oesophagus in 35.1% equally. The RF was performed at a median of 24 months (IQR 2.5 - 66 months) following prior fundoplication. Technique of RF included 17 (45.9%) conversions from full Nissen to partial anterior fundoplication (Dor), 10 (27.0%) re-do Nissen's, two (5.4%) conversions from full Nissen to partial posterior fundoplication's (Toupet), three (8.1%) complete reversal of fundoplication with oesophagogastric junction adhesiolysis, two (5.4%) Heller's myotomies with anterior fundoplication, two (5.4%) crural repairs only (intact wraps) and one (2.7%) opening of tight crura closure. The majority (83.8%) of revisions were completed laparoscopically. The most frequent intraoperative findings included significant oesophagogastric adhesions with wrap distortion (75.7%), recurrent crural defect (51.4%), slipped wrap (45.9%), distal oesophageal/crural fibrosis (37.8%), recurrent sliding hernia (35.1%), a tight crural inlet (24.3%), mixed herniation (10.8%) and three (8.1%) para-oesophageal hernias. Conclusion: This single-center review on revision fundoplication conforms with much of what is written in other studies. Dysphagia is the predominant symptom prompting repeat surgery and most patients present two years after their initial operation. Despite revision anti-reflux surgery remaining technically challenging, the vast majority of operations were completed laparoscopically with low associated morbidity. Larger, multi-center studies would allow for a bigger picture of revision anti-reflux surgery in the greater South African context.